RANDOM CLOSED SET MODELS: ESTIMATING AND SIMULATING BINARY IMAGES - Gallego, Ángeles M; Simó, Amelia (Image Analysis and Stereology, 2011)
In this paper we show the use of the Boolean model and a class of RACS models that is a generalization of it to obtain simulations of random binary images able to imitate natural textures such as marble or wood. The different tasks required, parameter estimation, goodness-of-fit test and simulation, are reviewed. In addition to a brief review of the theory, simulation studies of each model are included.